2012
DOI: 10.3899/jrheum.111229
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study of Mycophenolate Mofetil Treatment in Progressive Diffuse Cutaneous Systemic Sclerosis of Recent Onset

Abstract: Objective.A prospective observational study of mycophenolate mofetil (MMF) treatment in patients with diffuse progressive cutaneous systemic sclerosis (SSc) of recent onset.Methods.Twenty-five previously untreated consecutive patients with recent-onset (< 24 mo) diffuse progressive cutaneous SSc received MMF as the only disease-modifying therapy. Modified Rodnan skin score (mRSS) and affected body surface area (BSA) were compared from initiation of MMF to study end. Pulmonary function tests performed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 27 publications
4
51
3
2
Order By: Relevance
“…17 In this prospective, observational study of 42 patients with diffuse skin disease taking MMF for the primary indication of skin thickening, MMF was associated with modest improvements in skin scores with a fall in mean mRSS of 3.7 at 12 months and 7.6 at 24 months. This concurs with the findings of Mendoza et al, 7 who demonstrated a mean fall in mRSS of 10.9 after 18 months of MMF therapy in 25 patients with early disease (< 2 years), with a reduction in accumulation of fibrotic tissue as well as real-time polymerase chain reaction demonstrating reduced expression of fibrosisrelated genes in skin biopsies. In a larger, retrospective study by Le et al 9 of 98 patients with a median disease duration of 12.5 months and a baseline mRSS of 23 and a smaller prospective study by Derk et al 8 of 15 patients with a mean disease duration of 13.4 months and baseline mRSS of 22, skin score reductions of 7.9 and 14, respectively, were seen at 12 months.…”
Section: Tolerabilitysupporting
confidence: 80%
See 3 more Smart Citations
“…17 In this prospective, observational study of 42 patients with diffuse skin disease taking MMF for the primary indication of skin thickening, MMF was associated with modest improvements in skin scores with a fall in mean mRSS of 3.7 at 12 months and 7.6 at 24 months. This concurs with the findings of Mendoza et al, 7 who demonstrated a mean fall in mRSS of 10.9 after 18 months of MMF therapy in 25 patients with early disease (< 2 years), with a reduction in accumulation of fibrotic tissue as well as real-time polymerase chain reaction demonstrating reduced expression of fibrosisrelated genes in skin biopsies. In a larger, retrospective study by Le et al 9 of 98 patients with a median disease duration of 12.5 months and a baseline mRSS of 23 and a smaller prospective study by Derk et al 8 of 15 patients with a mean disease duration of 13.4 months and baseline mRSS of 22, skin score reductions of 7.9 and 14, respectively, were seen at 12 months.…”
Section: Tolerabilitysupporting
confidence: 80%
“…This is in contrast to other studies of MMF in the treatment of SSc-ILD which showed modest improvements in FVC; 7,8,[23][24][25] however, this can be explained by the high baseline FVC in our cohort and the low rates of concurrent, progressive ILD. Oral aperture also remained unchanged over the period of follow-up.…”
Section: Tolerabilitycontrasting
confidence: 53%
See 2 more Smart Citations
“…Although the toxicity of MMF appears tolerable, the longterm toxicity of MMF in this setting remains unknown. Whether MMF has additional disease-modifying benefits such as in improving the cutaneous involvement of SSc remains unclear 13,14,15,16 . Finally, as the authors note, it is unclear how long patients should be treated with MMF to avoid progression of lung fibrosis.…”
mentioning
confidence: 99%